Evaluation of blasting activities to achieve rock fragmentation targets ≤ 50 cm at PT. Lotus SG Lestari. - Syiffa Lutfi Fitri; Supriyadi Supriyadi; M Bambang Soegeng (Jurnal Inovasi Pertambangan dan Lingkungan, 2021)
The study aims to optimize blasting geometry in order to obtain optimal fragmentation where the preccentage of boulders is less than 15%. The study method is carried out by providing recommendations for blasting geometry based on the theory of R.L. Ash and C.J.Konya and analysis were carried out based on the Kuz-Ram equation and software split desktop in determining rock fragmentation in order to obtain an optimal blasting geometry plan. As a result, the blasting geometry of R.L. Ash has been more effective and efficient to apply. This indicated by the boulder of fragmentation is produced 14%.